1995
DOI: 10.1007/bf01088328
|View full text |Cite
|
Sign up to set email alerts
|

A study on the nutritional status of adolescent girls

Abstract: One hundred and twenty school girls in the age group of 13-15 years from four Government schools of Ludhiana city were selected for the study. On the basis of their family income they were divided into three experimental groups i.e. income group I (IgI), income group II (IgII) and income group III (IgIII). The results showed that the intake was low for all the foods. However, the consumption of fruits, milk and milk-products, sugar and jaggery, fats and oils by the subjects of IgII and IgIII was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…This is similar to the study done in Faridabad, Haryana 8 found that 93.5% adolescents were below the BMI 18.5. These finding are similar to various other studies 2,6,9,10,11 where they also found most of the girls were undernourished or below the BMI 18.5.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to the study done in Faridabad, Haryana 8 found that 93.5% adolescents were below the BMI 18.5. These finding are similar to various other studies 2,6,9,10,11 where they also found most of the girls were undernourished or below the BMI 18.5.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study the 95th percentiles for 24-h urinary calcium excretion and calcium/creatinine ratio were 2.2 mg/kg and 0.15, respectively. The low levels of urinary calcium excretion were possibly due to its deficient dietary intake, as observed in this and other studies from north India [18,20].…”
Section: Discussionmentioning
confidence: 65%
“…[8] Although prevalence of Anaemia is marginally higher in rural areas but some recent studies have highlighted the increasing prevalence of Anaemia among adolescents living in urban settlements. [9,10] Measuring height, weight, and body mass index (BMI) gives significant information on the nutritional and health status of individuals. Many research studies have reported that malnutrition affects body growth and development, especially during the crucial period of adolescence.…”
Section: Introductionmentioning
confidence: 99%